2017
DOI: 10.21873/anticanres.11641
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic HCV RNA Level and Genotype 1 Independently Associate with Hepatic Reticulon 3 Expression

Abstract: Abstract. Background /Aim: Reticulon 3 (RTN3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A recent report revealed increased intrahepatic RTN3 expression which correlated with higher HCV genotype 1 RNA levels [ 37 ]. Further, conflicting reports have indicated that RTN3 knockdown in cells can lead to either an increase [ 29 ] or no change [ 30 ] in intracellular HCV RNA levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report revealed increased intrahepatic RTN3 expression which correlated with higher HCV genotype 1 RNA levels [ 37 ]. Further, conflicting reports have indicated that RTN3 knockdown in cells can lead to either an increase [ 29 ] or no change [ 30 ] in intracellular HCV RNA levels.…”
Section: Resultsmentioning
confidence: 99%
“…In Flaviviruses, RNT3 was shown to be significantly enriched within membranous structural sites of virus replication [ 28 , 43 ]. In the context of HCV infection, Lin et al revealed increased intrahepatic RTN3 levels which correlated with higher HCV genotype 1 RNA levels [ 37 ]. These observations are in concert with our findings which revealed increased RTN3L&S isoforms in HCV JFH1 infected Huh7 cells and liver samples from HCV infected treatment naïve individuals.…”
Section: Discussionmentioning
confidence: 99%
“…FAM134B, SEC62, RTN3 and CCPG1) identified to be associated with the ER autophagy. Among these receptors, FAM134B, SEC62 and RTN3 have been reported to be closely related to the pathogenesis of HCC (Lin et al 2017;Du et al 2019;Zhang et al 2019). These lead us to investigate the possible clinicopathological and prognostic significance of CCPG1 in HCC.…”
Section: Introductionmentioning
confidence: 98%